Ten Years of Teaching Forgiveness Education in the Schools of Greece: Looking toward the Future - Peli Galiti (Education Sciences)
This article presents the accumulated experience and outcomes after ten years of forgiveness education (FE) in the schools of Greece. The author implemented the program throughout Greece by publishing new books on FE adapted to the Greek culture and training an interdisciplinary team of educators through both in-person and online workshops in several Greek cities. Using feedback from the experiences of the trained teachers and the participating students, a lot of valuable information was obtained for the future expansion of forgiveness education programs. Our objective is to provide a conceptual map for educators so that they may be better equipped when designing their own implementation plans for forgiveness education programs in other schools and countries. Dissemination practices and innovative methods are suggested. Recommendations for the future also include steps for the development and growth of FE in institutions and settings outside the school environment, thus spreading FE concepts and the resultant new ways of thinking and practices throughout the community.